National Stakeholder Orientation, Corporate Social Responsibility, and Bank Loan Cost - Cheung, Stephen Y. L.; Tan, Weiqiang; Wang, Wenming (2018)
Based on a sample of firms from 20 countries around the world, this study investigates how the relationship between corporate social responsibility (CSR) and bank loan pricing is affected by the degree of national stakeholder orientation. We find that firms with superior CSR performance are more likely to enjoy lower loan costs in more stakeholder-oriented countries than are their counterparts in less stakeholder-oriented countries. This study contributes to the CSR literature by highlighting the importance of national institutional environments in determining the economic consequences of CSR practices.
Keywords: National stakeholder orientation; Bank loan pricing; Corporate Social Responsibility